Kinerja Mobilisasi Bahan Dan Peralatan Pada Pekerjaan Konstruksi : Studi Kasus Pembangunan Jalur Kereta Api Lintas Makassar-Parepare - Andi Sri Rezeky Aprillia S; Ahmad Yauri Yunus; Savitri Prasandi Mulyani (Jurnal Penelitian Teknik Sipil Konsolidasi, 2023)
The purpose of this study was to analyze the effect of the performance of the mobilization of materials and equipment, the advantages of mobilizing materials and equipment and the weaknesses of the mobilization of materials and equipment on the mobilization of materials and equipment and to determine the most influential variables. This study uses quantitative methods with the number of respondents as many as 55 people. The instrument testing uses validity and reliability tests, while the data analysis method uses multiple linear regression with the F test and t test. The results showed that the variables of Material and Equipment Mobilization Performance (X1), Excess Mobilization of Materials and Equipment (X2) and Weaknesses of Materials and Equipment (X3) simultaneously affected the Mobilization of Materials and Equipment Equipment (Y), Based on the t-test, the variable Performance Mobilization of Materials and Equipment (X1), Advantages of Mobilization of Materials and Equipment (X2), and Weaknesses of Mobilization of Materials and Equipment (X3) have a positive and significant effect on Mobilization of Materials and Equipment (Y). and the value of Adjusted R Square which means the influence of the independent variable on the dependent variable is 71.4%.